If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-1-3=5x+3
We move all terms to the left:
3x-1-3-(5x+3)=0
We add all the numbers together, and all the variables
3x-(5x+3)-4=0
We get rid of parentheses
3x-5x-3-4=0
We add all the numbers together, and all the variables
-2x-7=0
We move all terms containing x to the left, all other terms to the right
-2x=7
x=7/-2
x=-3+1/2
| 4x-7=x+10x= | | 31 (x+53 )=56 | | 4x-6=2x+8, | | 7(2a-6)=70 | | 8w+1=49 | | 6m+8=41-5 | | 7=3s−8 | | 11x-4=-9 | | 31.4=6.28*r | | 3x-2.4=7.2 | | 4(4+x)=3(3+8) | | 10=x+9/2+3x+7/4 | | 2r+4+4r+8=26 | | 5(k+2)=-50 | | –12+2z=2 | | 3x-2x=25-11 | | 4(x+11)=48 | | 25x+4x=x | | x+4/3=19 | | -4+3s=2 | | 3xx-7=2xx5 | | 7x+3x^2=1340 | | (8x-3=5x+6) | | -6(x+5)+3=2(x+4)-4x | | y=+12 | | 2(2y=+7)=42 | | 2/5x-2/5=-3x-3/2 | | 7m+20=50-3 | | -4w+4=20 | | 9.2x=-27.6 | | (5+x)+x=150 | | 8n+15=5n-45 |